PENERAPAN MODEL INKUIRI TERBIMBING TERHADAP KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK - Nuraini Sukahar; Bunga Dara Amin; Khaeruddin Khaeruddin (Charm Sains: Jurnal Pendidikan Fisika, 2023)
This research is a pre-experimental study that aims to determine the difference in the value of students' critical thinking skills before being taught using the guided inquiry learning model and after being taught using the guided inquiry learning model to students in class XI MIPA at SMA Negeri 10 Maros. The independent variable in this study is the guided inquiry learning model, while the dependent variable is students' critical thinking skills. The population in this study were all students in class XI MIPA at SMA Negeri 10 Maros, totaling 72 people and divided into 3 classes, while the samples in this study were class XI MIPA 2, totaling 24 people and class XI MIPA 3, totaling 25 people. The research data were obtained by giving tests of critical thinking skills to students in the form of pretest and posttest. Based on the results of the descriptive analysis, the average score obtained before being given treatment to students was 3.65, while the average score after being given treatment to students was 9.35. The results of the analysis using inferential statistics obtained an n-gain test value of 0.73 which is included in the "High" category, with a percentage of 73% and is included in the "Quite Effective" category.